STUDI PENGGUNAAN AGREGAT HALUS PASIR DAN AGREGAT KERIKIL ALAM SUNGAI BATANGHARI TERHADAP KUAT TEKAN BETON - Putri Della Safera; M Nuklirullah; Fetty Febriasti Bahar (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Concrete is a widely used construction material due to its high strength and durability. The quality of concrete is greatly influenced by the characteristics of the aggregates that make up 60–70% of the concrete volume. This study aims to analyze the effect of fine sand aggregate and coarse natural gravel aggregate from the Batanghari River on the compressive strength of concrete. Three sample variations were used, namely: AA (Mendapo Quarry and Kasang Quarry aggregates), BB (RBE Quarry and Sengeti Quarry aggregates), and AABB (a combination of AA + BB). The test specimens were cylindrical in shape, measuring 15×30 cm with a design quality of 20 MPa. Compressive strength testing was carried out at the ages of 7, 14, and 28 days according to SNI 1974:2011. The test results at 7 days of age were 5.436 MPa for AA samples, 5.067 MPa for BB samples, 5.879 MPa for AABB samples, at 14 days of age 16.080 MPa for AA samples, 13.389 MPa for BB samples, 14.829 MPa for AABB samples and at 28 days of age 20.907 MPa for AA samples, 17.403 MPa for BB samples and 22.036 MPa for AABB samples which produced the highest compressive strength. The combination of aggregates provides better gradation, low porosity, and higher density. The natural aggregates of Batanghari River are proven to be suitable for use in medium quality concrete.